Analysis, modelling and implementation of multi-phase single-leg DC/DC converter for fuel cell hybrid electric vehicles. (3rd July 2020) - Mallikarjuna Reddy, Bandi; Samuel, Paulson
ABSTRACT: Multi-phase converter topologies for use in high-power density applications such as fuel cell hybrid electric vehicles (FCHEVs) have received huge interest in recent years. In this paper, a multi-phase interleaved structure and its control has been proposed for use with a PEMFCHEV to decrease the current ripples of the interleaved inductors, the output voltage ripples of the bus capacitor, and the size and weight of their passive components with higher efficiency compared with the conventional boost converter (CBC) and two-phase interleaved boost converter (TPIBC). Furthermore, the fuel cell stack and the lithium-ion (Li-ion) battery are connected to the same DC voltage bus through a multi-phase single-leg (MPSL) converter and a resonant dual active bridge isolated bidirectional DC/DC converter (RDAB-IBDC), respectively. The proposed DC/DC converter topology and its controller is designed and investigated by using PSCAD (4.6.0) simulator. The proposed DC/DC converter is experimentally validated with results obtained from a prototype set-up that has been built and tested in the laboratory based on dSPACE (RTI1104). Finally, the simulation and experimental results have shown that the proposed converter is more effective than other DC/DC converter topologies and achieves higher performance and reliability for high-power density DC/DC converters.